Inspiratory muscle training at sea level improves the strength of inspiratory muscles during load carriage in cold-hypoxia. Issue 12 (1st December 2020) - Hinde, K. L.; Low, C.; Lloyd, R.; Cooke, C. B.
Abstract: Inspiratory muscle training (IMT) and functional IMT (IMTF : exercise-specific IMT activities) has been unsuccessful in reducing respiratory muscle fatigue following load carriage. IMTF did not include load carriage specific exercises. Fifteen participants split into two groups (training and control) walked 6 km loaded (18.2 kg) at speeds representing ∼50%V̇O2max in cold-hypoxia. The walk was completed at baseline; post 4 weeks IMT and 4 weeks IMTF (five exercises engaging core muscles, three involved load). The training group completed IMT and IMTF at a higher maximal inspiratory pressure (Pimax ) than controls. Improvements in Pimax were greater in the training group post-IMT (20.4%, p = .025) and post-IMTF (29.1%, p = .050) compared to controls. Respiratory muscle fatigue was unchanged ( p = .643). No other physiological or subjective measures were improved by IMT or IMTF . Both IMT and IMTF increased the strength of respiratory muscles pre-and-post a 6 km loaded walk in cold-hypoxia. Practitioner Summary: To explore the interaction between inspiratory muscle training (IMT), load carriage and environment, this study investigated 4 weeks IMT and 4 weeks functional IMT on respiratory muscle strength and fatigue. Functional IMT improved inspiratory muscle strength pre-and-post a loaded walk in cold-hypoxia but had no more effect than IMT alone. Abbreviations: ANOVA: analysis of variance; BF: breathing frequency; CON: control group; EELV: end-expiratory lung volume; EXP: experimental group; FEV1 : forced expiratory volume in one second; FiO2 : fraction of inspired oxygen; FVC: forced vital capacity; HR: heart rate; IMT: inspiratory muscle training; IMTF : functional inspiratory muscle training; Pemax : maximal expiratory pressure; Pimax : maximal inspiratory pressure; RMF: respiratory muscle fatigue; RPE: rate of perceived exertion; RWU: respiratory muscle warm-up; SaO2 : arterial oxygen saturation; SpO2 : peripheral oxygen saturation; V̇E: minute ventilation; V̇O2 : rate of oxygen uptake